Employee training and development, an HRM Practice: A Review - Mehta, Aarti (Innovative Research Thoughts, 2017)
The success of every company is heavily dependent on its personnel in every industry. Other factors play a significant role, such as ensuring an organization's efficient staff are aligned with its financial dominance and market position. Because of this, firms must pay attention to employee happiness and retention in order to preserve their most important human resource. Some firms believe that workers are exclusively interested in financial gain. While this remark may be true, it ignores the enormous value that most workers put on the intrinsic advantages of their jobs. Consequently, it has a negative impact on not just employee happiness and retention, but on the companies as well. Employees that can quickly adapt to a changing business environment should be a must for any company. Investing heavily in staff training and development is now the norm for most businesses, since it is the only way to stay competitive and profitable. Organizations are increasingly relying on training as a way to compete with their rivals in the marketplace.